(3cJGH Gdbhd GdHOjY aj aVd GdUdGI hGdSdGe Ydi GdMHjH GdTajYs - (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa bOQ SjOfG eMeO GdQShd GdcQje hNUg HGdUdGI hGdJSdje hCeQfG HPdc ai GdbQBf GdMcje GdHGH GdChd ai GdCeQ HGdUdGI Ydi QShd Gddg Udi Gddg Ydjg hSde hcjajI Pdc Ydi ENJdGa CfhGYI s
(3BNQgG (B:s
(3hef CSeGA GdQLGd JgPjH GdJgPjH dTjNfG hdSGf GdejRGf dg BNQ cJGH Gdbhd GdHOjY ai GdUdGI Ydi GdMHjH GdTajY s
(3HgG fXGe GdJYbjHIs
(3cJHJ ai MjGI GdeDdas
(3cJHJ GdcQGSI GdChdi HNW bOje eZGjQ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs